2018
DOI: 10.1111/cch.12576
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review to explore how universal design for learning is described and implemented by rehabilitation health professionals in school settings

Abstract: This scoping review provides a broad understanding of how RHPs describe and implement UDL-aligned services in school settings. UDL is a promising framework that provides RHPs with guidance on how to support children with diverse needs in the classroom, with the overall aim to promote inclusion of all children. There is a need for further research to determine the effectiveness of UDL as implemented by RHPs and to examine the role of physiotherapists in using UDL-type services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…Nineteen (83%) of 23 identified studies reported significant benefits on at least one aspect of motor skill. A variety of motor skill domains were improved via a number of different interventional approaches, including fully inclusive and potentially less stigmatizing whole class approaches (Kennedy et al, ), as well as more targeted interventions for children with recognized motor difficulties. Although the majority of these interventions were teacher led, the use of technology such as iPads for motor skill instruction (Axford et al, ; Chang & Yu, ), and more interdisciplinary methods were also trialled (Case‐Smith, Holland, et al, ; Case‐Smith, Weaver, et al, ; Donica, ; Ohl et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen (83%) of 23 identified studies reported significant benefits on at least one aspect of motor skill. A variety of motor skill domains were improved via a number of different interventional approaches, including fully inclusive and potentially less stigmatizing whole class approaches (Kennedy et al, ), as well as more targeted interventions for children with recognized motor difficulties. Although the majority of these interventions were teacher led, the use of technology such as iPads for motor skill instruction (Axford et al, ; Chang & Yu, ), and more interdisciplinary methods were also trialled (Case‐Smith, Holland, et al, ; Case‐Smith, Weaver, et al, ; Donica, ; Ohl et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations: E R/W T, Elementary Read/Write Test (Hung, Chang, Chen, Chen, & Lee, 2003); ETCH-M, Evaluation Tool of Children's Handwriting-Manuscript (Amundson, 1995); HHRA, Hebrew Handwriting Readiness Assessment, (Erez & Parush, 1999); MHA, Minnesota Handwriting Assessment (Reisman, 1999); OT, occupational therapist; PAL-II, Process Assessment of the Learner, 2nd Edition, (Berninger, 2007); THS-R, Test of Handwriting Skills-Revised (Milone, 2007); identified studies reported significant benefits on at least one aspect of motor skill. A variety of motor skill domains were improved via a number of different interventional approaches, including fully inclusive and potentially less stigmatizing whole class approaches (Kennedy et al, 2018), as well as more targeted interventions for children with recognized motor difficulties. Although the majority of these interventions were teacher led, the use of technology such as iPads for motor skill instruction (Axford et al, 2018;Chang & Yu, 2014), and more interdisciplinary methods were also trialled Case-Smith, Weaver, et al, 2014;Donica, 2015;Ohl et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Our multidisciplinary team of researchers and clinicians with expertise in tiered approaches to school-based rehabilitation functioned as the expert panel. Panel members had both published and reviewed relevant literature prior to convening for a participatory roundtable discussion (e.g., Campbell et al, 2016Campbell et al, , 2012Kennedy et al, 2018;Missiuna et al, , 2012Missiuna et al, , 2016Missiuna et al, , 2012Pollock, Dix, Whalen, Campbell, & Missiuna, 2017). An impartial experienced independent researcher (SV), hired to conduct data analysis, facilitated the roundtable discussion to elicit assumptions related to tiered services.…”
Section: Expert Consultation and Literature Reviewmentioning
confidence: 99%
“…Our quantitative results indicate that therapists spent the majority of their time on Level 1 activities, as would be expected in this new model of service delivery, and based on the model’s core principles. The therapists used practices inspired by UDL approaches, and performed observations and conducted workshops as previously reported ( Kennedy et al, 2018 ). Qualitative results highlight, however, the difficulties for therapists when determining which of their actions are associated with what specific activity level, given how integrated activity levels may be within the model and how often actions overlap with collaboration and relationship-building activities.…”
Section: Discussionmentioning
confidence: 99%
“…UDL is a specific framework that can be employed when providing Level 1 services as part of an RtI model. Specifically, UDL can foster collaboration between health and education professionals to support the inclusion of students with disabilities into general education classrooms ( Kennedy et al, 2018 ). It is only relatively recently that RtI and UDL have begun to influence occupational therapy practice, for instance, to support children with autism in schools ( Grandisson et al, 2019 ; Missiuna et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%